How does COVID-19 pandemic affect entrepreneur anxiety? The role of threat perception and performance pressure - Li, Yunjian; Chen, Hongchuan; Liu, Chunzhen; Liu, Hong (Frontiers in Psychology, 2022)
The entrepreneurial firms may be more vulnerable to the COVID-19 pandemic, and the entrepreneurs of entrepreneurial firms are also threatened by the revenues decline and business failure, which vehemently affect their well-being. The mental health of the entrepreneur decides whether the entrepreneurial firms can make the right decision, which is related to the healthy development of the entrepreneurial firms. Based on the event system theory and the cognitive appraisal theory, this paper aims to explore the effect of COVID-19 pandemic on the entrepreneur anxiety, and the threat perception and performance pressure are introduced to investigate the mediating mechanism and boundary of this effect. Using the simple random sampling to obtain questionnaire survey data, 168 entrepreneurs of entrepreneurial firms have participated in the empirical study, and the research results are as follows. First, the COVID-19 pandemic significantly positively affects entrepreneur anxiety. Second, the entrepreneur threat perception plays a mediating role between the COVID-19 pandemic and the entrepreneur anxiety, which means the COVID-19 pandemic can enhance the external threat perception of entrepreneurs, and then affect the entrepreneur anxiety. Third, the positive effect of the COVID-19 pandemic on the entrepreneur anxiety is strengthened by the entrepreneur performance pressure, while the positive effect of entrepreneur threat perception on entrepreneur anxiety is weakened by the entrepreneur performance pressure. The above findings are helpful to explore the mechanism of the COVID-19 pandemic and other critical crisis events on entrepreneurs’ mental health from the new perspective of cognitive appraisal theory and event system theory, filling the research gaps between the COVID-19 pandemic and entrepreneur anxiety. Besides, this study broadens the applied range of the cognitive appraisal theory and the event system theory in the fields of crisis situations and entrepreneur research, and enriches the research outputs. Furthermore, this study will help provide a new theoretical analysis insight for the related research on how the COVID-19 pandemic affects entrepreneurs’ psychology, and further deepen researchers to understand the mechanism of entrepreneur anxiety under the COVID-19 pandemic, providing theoretical inspirations for reducing entrepreneur anxiety. What’s more, this study finds that individual pressure can affect their cognitive appraisal, which means that future research should take the pressure influential mechanism into consideration in the process of exploring “external stimulus--cognitive appraisal--emotional response,” further expanding the theoretical model of cognitive appraisal proposed from the perspective of pressure.